2016
DOI: 10.1016/j.triboint.2015.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased load on the wear of a large diameter metal-on-metal modular hip prosthesis with a high inclination angle of the acetabular cup

Abstract: This is an electronic reprint of the original article. This reprint may differ from the original in pagination and typographic detail. Author(s):Saikko, Vesa Title: Effect of increased load on the wear of a large diameter metal-on-metal modular hip prosthesis with a high inclination angle of the acetabular cup All material supplied via Aaltodoc is protected by copyright and other intellectual property rights, and duplication or sale of all or part of any of the repository collections is not permitted, excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
(58 reference statements)
1
14
0
Order By: Relevance
“…2 of test 2 from (Saikko, 2016a). Hence, the test was a continuation of the earlier, adverse condition, 3 million cycle wear test with a 3 kN peak load, in which the wear rate was as high as 150 mg/10 6 cycles.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…2 of test 2 from (Saikko, 2016a). Hence, the test was a continuation of the earlier, adverse condition, 3 million cycle wear test with a 3 kN peak load, in which the wear rate was as high as 150 mg/10 6 cycles.…”
Section: Methodsmentioning
confidence: 96%
“…Two different load profiles were used so that the peak load value was either 2 kN or 3 kN (Saikko, 2015;Saikko, 2016a). The former was considered a normal value, and the latter an increased value caused by obesity (Bergmann et al, 2001;Bergmann et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saikko [30] demonstrated that under adverse loading conditions the gravimetric wear rate was not able to show a difference in performance of simulator tested hard-on-hard bearings unless the testing conditions passed a so-V et al [31] have also shown evidence of material degradation in hard-on-hard bearings with AgCrN coatings, despite no visible damage or gravimetric mass loss. Changes of the sliding regime to anything representing less than ideal conditions (i.e.…”
Section: Standard Gait Vs Microseparationmentioning
confidence: 99%
“…As discussed, the industry and research community are becoming increasingly interested in the effects of adverse loading situations and daily living activities on the performance of total hip replacements [23,24,30,31]. A continuous simple twin-peak profile may not be the best method for assessing these devices before they are implanted in patients.…”
Section: Standard Gait Vs Microseparationmentioning
confidence: 99%